Congenital Vascular Ring: Overcoming Perioperative Challenges - Chong, Soon Eu; Ali, Saedah; Mohd Zain, Mohd Rizal; Mamat, Ahmad Zuhdi; Shamsuddin, Ahmad Mahir; Mat Hassan, Mohd Erham (2016)
a two month old girl was admitted for ventricular septal defect (VSD) with heart failure and pulmonary hypertension. She had suffered from occasional stridor and fast breathing since birth. Echocardiography found a double aortic arch, and confirmed with 3D reconstructed thoracic computed tomography angiography (CTA).